The Id Aspect of the Major Characters in Sindhunata’s Novel Anak Bajang Menggiring Angin - Aulia Aulia; Seli Sesilia; Effendy Chairil (Journal of linguistics, culture and communication, 2026)
This study examines the id aspect of the major characters in Sindhunata’s novel Anak Bajang Menggiring Angin through the perspective of psychoanalytic literary studies. The purpose of this research is to reveal how instinctual drives influence the psychological dynamics, conflicts, and actions of the characters within the narrative. The study employs a descriptive qualitative method with a literary psychology approach. The data are derived from textual elements of the novel, including narration, dialogue, and character actions that indicate impulsive desires, emotional reactions, and instinctive behavior associated with the id. The analysis shows that the id appears in various forms such as desire, anger, aggression, ambition, and affective needs. Rahwana represents a dominant and destructive id, manifested through excessive ambition, lust for power, and uncontrolled impulses that lead to moral and social chaos. In contrast, Rama, Sinta, and Anoman demonstrate more restrained expressions of the id, where instinctual drives are moderated and transformed into ethical actions and moral strength. These differences highlight the role of the id as a fundamental psychological force that shapes character development and narrative tension. The findings indicate that the id functions not only as a source of destructive impulses but also as an essential element that drives human motivation and inner struggle. Through this portrayal, the novel reflects the complexity of human instincts and their influence on moral decision-making and character psychology.